Advances in the Field of Automated Essay Evaluation - Zupanc, Kaja; Bosnic, Zoran (Informatica, 2016)
Automated essay evaluation represents a practical solution to a time-consuming, labor-intensive and expensive activity of manual grading of students' essays. During the last 50 years, many challenges have arised in the field, including seeking ways to evaluate the semantic content, providing automated feedback, determining validity and reliability of grades and others. In this paper we provide comparison of 21 state-of-the-art approaches for automated essay evaluation and highlight their weaknesses and open challenges in the field. We conclude with the findings that the field has developed to the point where the systems represent a useful complement (not replacement) to human scoring.